Artificial intelligence empowers secondary school mathematics teaching: innovative design, intelligent evaluation, and effectiveness verification - Kamarudin, Nurzatulshima; Yang, Liu; Sulaiman, Tajularipin (Faculty of Educational Studies, 2025)
In the context of artificial intelligence reshaping educational practices, this study focuses on secondary school mathematics teaching and proposes an AI-empowered framework integrating “innovative design, intelligent evaluation, and effectiveness verification.” First, based on large language models and generative AI tools, a teaching design process tailored for secondary mathematics is outlined： the process leverages a knowledge graph to deconstruct the logical structure of mathematics, employs structured prompts to guide generative AI in producing pedagogically sound instructional content, and utilizes step-by-step scoring and error-type classification from learner responses to enable dynamic optimization of the design. Building on this process, the study develops a secondary mathematics AI-empowered teaching design model comprising “teaching analysis, content generation, and dynamic optimization.” Second, an intelligent evaluation index system is established to assess the accuracy, relevance, and technological value-added of AI-generated designs through multi-dimensional quantitative measures, thereby driving continuous iterative improvement. Finally, a verification plan is proposed, combining controlled experiments, surveys, and classroom observations, to guide future evaluation of the classroom effectiveness of AI-generated teaching designs. The study provides methodological pathways and assessment tools for the controlled implementation of AI in secondary mathematics classrooms.